Small towns in Lower Silesia during the pandemic – selected issues - Korenik, Stanisław; Kozak, Alicja (Małe miasta Dolnego Śląska w okresie pandemii – wybrane zagadnienia, 2024)
Aim: The aim of the article is to assess and illustrate the extent of variation in the functioning of small towns in Lower Silesia in socio-economic terms, including during the pandemic period, in reference to earlier studies. Methods: The article employs a descriptive method, critical analysis of the subject literature, statistical methods, and empirical inference. Findings: The analyzed indicators in small towns tend to be less favorable than in the region as a whole. This does not apply to towns located within the Wrocław Functional Area or those whose functioning is based on specific endogenous resources. Implications and recommendations: As a consequence, the development gap between small towns and the region’s growth poles continues to widen. Actions aimed at stimulating endogenous resources in these towns are necessary. Originality/value: The originality of the research lies in identifying differentiated development paths, with many small towns experiencing a development crisis despite positive regional trends. Their lack of integration with the region’s socio-economic structures became particularly evident during the pandemic.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 39-48
Keywords: Dolny Śląsk